Stimulation of Plant Growth with an Aqueous Solution Activated by Glow Discharge Plasma - Belov, S. V.; Apasheva, L. M.; Danileiko, Yu. K.; Egorov, A. B.; Lobanov, A. V.; Lukanin, V. I.; Ovcharenko, E. N.; Savransky, V. V.; Shilin, L. G. (Biophysics (Oxford), 2020)
—This paper presents the results on the application of low-concentration aqueous solutions of strong electrolytes activated by glow discharge plasma for plant growth stimulation. We provide experimental evidence that these solutions can be used as an effective regulator of plant growth.